Levels of Leptin and IL-6 With Some Biochemical Parameters in Iraqi Obese Children - Asmehan Adnan AL- naqeeb1 , Salwa Gahzi Turki2 , Zahid Jasim Muhamed2, Wesam Hameed Ahmed3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Obesity in children is attended by increased circulating leptin concentrations. Girls have higher leptinConcentrations than boys. IL-6 levels related positively with BMI and percent fat mass (PFM).The Objective: Was to detect the serum IL-6 and levels of leptin among girls and boys as obese and otherbiochemical parameters related with obesity. Methodology: This study involved 60 children were classifiedinto 2 groups; 30 obese ones (fifteen girls and boys fifteen) and 30 control (fifteen girls and fifteen boys)with years of seven- fifteen old who attended to the Obesity Research and Treatment Unit/ Al kindy MedicalCollege, during the period January 2017 – July 2017. A clinical examination and diagnosis were done foreach patient by the consultant medical staff and the biochemical laboratory examination results (FBS, bloodurea, serum creatinine, lipid profile, serum GOT, serum GPT, SCa and uric acid) were as a routine work.They compared with 30 healthy children with approximate age with patients. The sera were assessed forIL-6 and leptin by an ELISA kit. Results: Showed no significant differences among obese children (boysand girls) except the GPT and GOT were both higher significantly (P<0.05) in male (42.46±34.27 and33.3±13.6) than in girls (53.6 ±75.1 and 29.9±14.1). Whereas, obese girls revealed a significant increasingin (STRIG 120.3±26.7 P?0.01, SLDL 89.3±25.5 P?0.05, GOT 33.1±13.6 P?0.01, GPT 29.9±14.1 P?0.01and LIPTIN 2758.4±539.1 P?0.001) in comparison to the control girls. Similarly, for boys highly significantincreasing appeared in (SLDL 90.92±18.1, GOT 42.46±34.27, GPT 53.6±75.1 and LIPTIN 2883.93±512.7P?0.001), as well as in STRIG .69±.13 P?0.05 then normal boys. Inversely, it has been shown that (BURIA26.7±5.3 P?0.05, SCREAT .69±.13 P?0.01 and SVLDL 20.15±6.3 P?0.01) were decreased significantly.In boys IL-6 showed significant positive correlation with BMI, while leptin revealed strong associated waswith IL-6 Conclusion: Obesity associated with elevated blood leptin and IL-6 levels. Leptin and IL-6 playkeys role as a biomarker for childhood obesity, and can help in the prediction of get weight in obese childrenas well as its important interrelationship with other parameters.